Hubungan fitur media digital dengan kepuasan mahasiswa dalam mengakses informasi program mobilitas internasional ITB - Syifa Fauziah Musyafa; Agus Rahmat; Efi Fadilah (Jurnal Praksis dan Dedikasi Sosial, 2026)
The relationship between digital media features and student satisfaction in accessing information on ITB’s international mobility program This study intends to analyze the relationship between digital media features and students’ satisfaction in accessing information about international mobility programs at Institut Teknologi Bandung. This research is grounded in Uses and Gratifications 2.0, particularly in the MAIN model in which it explains that digital media affordances involving modality, agency, interactivity, and navigability plays a role as sources of user gratification in new media environments. A quantitative approach was applied using a survey method involving ITB students who had accessed information about international mobility programs through IRO ITB digital platforms. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics. The findings indicate that digital media features are associated with students’ satisfaction in accessing institutional mobility information. More specifically, the findings suggest that clear information presentation, user control, interactive features, and ease of navigation are important aspects in enhancing students’ satisfaction with digital information services. Penelitian ini bertujuan untuk menganalisis hubungan antara fitur media digital dan kepuasan mahasiswa dalam mengakses informasi mengenai program mobilitas internasional di Institut Teknologi Bandung. Penelitian ini berlandaskan pada Uses and Gratifications 2.0, khususnya MAIN Model, yang menjelaskan bahwa affordances media digital yang meliputi modality, agency, interactivity, dan navigability berperan sebagai sumber gratifikasi pengguna dalam lingkungan media baru. Penelitian ini menggunakan pendekatan kuantitatif dengan metode survei yang melibatkan mahasiswa ITB yang pernah mengakses informasi mengenai program mobilitas internasional melalui platform digital IRO ITB. Data dikumpulkan menggunakan kuesioner berbasis skala Likert dan dianalisis melalui statistik deskriptif. Temuan penelitian menunjukkan bahwa fitur media digital berhubungan dengan kepuasan mahasiswa dalam mengakses informasi mobilitas institusional. Secara lebih spesifik, temuan penelitian menunjukkan bahwa kejelasan penyajian informasi, kendali pengguna, fitur interaktif, dan kemudahan navigasi merupakan aspek penting dalam meningkatkan kepuasan mahasiswa terhadap layanan informasi digital.